Learning-based tracking of fast moving objects - Zita, A.; Sroubek, F. (arXiv e-print repository, 2020)
Tracking fast moving objects, which appear as blurred streaks in video sequences, is a difficult task for standard trackers as the object position does not overlap in consecutive video frames and texture information of the objects is blurred. Up-to-date approaches tuned for this task are based on background subtraction with static background and slow deblurring algorithms. In this paper, we present a tracking-bysegmentation approach implemented using state-of-the-art deep learning methods that performs near-realtime tracking on realworld video sequences. We implemented a physically plausible FMO sequence generator to be a robust foundation for our training pipeline and demonstrate the ease of fast generator and network adaptation for different FMO scenarios in terms of foreground variations